Islamic Perspective on the Concept of a Sakinah Family in a Career Family - Ali, Ridwan; Hajrah, Hajrah (LPPM Institut Studi Islam Sunan Doe, 2024)
This study aims to examine the Islamic perspective on the concept of a sakinah family in a career family. The method used in this research is the literature review method by collecting data from various trusted literary sources such as scientific journals, books, articles, and websites. After the data is collected, the researcher synthesizes the data by summarizing the relevant information and combining it in the form of conclusions and suggestions. The results of the study show that the concept of a sakinah family in a career family is very relevant to Islamic teachings. A sakinah family is defined as a family that maintains harmony and brings blessings. In the context of a career family, there are several factors that can affect family harmony such as long working distances, high job demands, and excessive use of technology. However, Islam provides several values that can help maintain family harmony in the career family context, such as the values of simplicity and justice that must be upheld in the family. Apart from that, Islam also emphasizes the importance of good communication within the family and helping each other in overcoming the challenges they face.